PWE-136 The non-invasive detection of non-alcoholic fatty liver disease using urinary volatile organic compound analysis: a pilot study. (22nd June 2015) - Covington, J; Mcfarlane, M; Daulton, E; Westenbrink, E; O'Connell, N; Wurie, S; Nwokolo, C; Bardhan, KD; Savage, R; Arasaradnam, R
Abstract : Introduction: Non Alcoholic Fatty Liver Disease (NAFLD) is the commonest cause of chronic liver disease in the western world. Current diagnostic methods, including that of the Fibroscan, have limitations, thus there is a clinical need for more robust, non-invasive screening tools. The gut microbiome is altered in several gastrointestinal and hepatic disorders resulting in altered, unique gut fermentation patterns. These patterns are detectable by analysis of volatile organic compounds (VOCs) in urine, breath and faeces. We aimed to determine if progressive fatty liver disease produced an altered VOC pattern in urine; specifically NAFLD and Non-Alcoholic Steatohepatitis (NASH). Method: 34 patients were recruited; 8 NASH cirrhotics (NASH-C); 7 non-cirrhotic NASH; 4 NAFLD and 15 controls. Urine was collected and stored frozen. For assay, the samples were defrosted and aliquoted into vials, which were heated to 40 ± 0.1°C and the headspace analysed by FAIMS (Field Asymmetric Ion Mobility Spectroscopy). A previously used data processing pipeline employing a 'Random Forrest' classification algorithm and a 10 fold cross validation method was applied. Results: Urinary VOCs could distinguish liver disease patients from controls with a sensitivity of 0.58 (0.33–0.88) but specificity of 0.93 (0.68 – 1.00); Area Under Curve (AUC) 0.73 (0.55 – 0.90). NASH/NASH-C was similarly separated from the NAFLD/control patients with a sensitivity of 0.73 (0.45–0.92), a specificity of 0.79 (0.54–0.94) and AUC of 0.79 (0.64–0.95), respectively. Conclusion: This pilot study offers the potential for early non-invasive tracking of liver disease using urinary VOC bio-odorant fingerprints to distinguish patients with a disease within the spectrum of fatty liver disease from healthy controls, but also to distinguish subsets of the spectrum from each other, such as NASH from NAFLD. This may develop into a viable alternative surveillance or diagnostic tool in patients unable or unwilling to undergo liver biopsy. Disclosure of interest: None Declared.